Effect of electrical treatment on structural behaviors of gelled waxy crude oil. (1st October 2019) - Li, Hongying; Wang, Xinyi; Ma, Chenbo; Lu, Yingda; Han, Shanpeng; Chen, Chaohui; Zhang, Jinjun
Highlights: Effect of electrical treatment on structure of waxy gel was firstly investigated. Structural strength of waxy gel can be weakened after electrical treatment. Treatment temperatures needs to be lower than WAT to obtain changes on gel. Lower temperature and higher field strength favor better treatment effect. Electrical treatment has no influence on the phase equilibrium of wax in crude oil. Abstract: Waxy crude oil presents poor flowability and complicated rheological behaviors near and below its gelation temperature. In recent years, high voltage direct current electric field has emerged as a novel approach to significantly reduce the viscosity of waxy crude oil below its wax appearance temperature, but the effect of electrical treatment on the structural behaviors of gelled waxy crude oil remains unknown. In the present study, the viscoelasticity, yielding behavior, and thixotropy of gelled waxy crude oil experienced electrically-treatment were investigated over a range of electrical field strength of 0–0.8 kV/mm and treatment temperature between the wax appearance temperature and the pour point. We demonstrate for the first time that the structural strength of gelled waxy crude oil can be significantly weakened after electrical treatment below its wax appearance temperature. The magnitude of the reduction increases with the electric field strength increasing and treatment temperature decreasing. However, no significant influence was found on the wax appearance temperature, wax disappearance temperature, and the amount of precipitated and dissolved wax, revealing the phase equilibrium of wax in crude oil not affected. The investigation of the wax crystal microscopy shows that the wax crystals in the electrically-treated waxy gels are generally larger, and have larger aspect ratio and boundary box fractal dimension, which indicates that the size and morphology of wax crystals are varied by the influence of the electrical treatment.